2022
DOI: 10.1038/s41598-022-18077-z
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric nutritional risk index as a potential prognostic marker for patients with resectable pancreatic cancer: a single-center, retrospective cohort study

Abstract: In pancreatic cancer, postoperative complications (POCs) are associated with disease outcomes. The geriatric nutritional risk index (GNRI) is known to predict POCs after pancreatoduodenectomy (PD) or distal pancreatectomy (DP) in patients with hepatobiliary pancreatic tumors, including pancreatic cancer. Through POC occurrence risk, we aimed to determine whether GNRI could predict prognosis in patients who underwent PD or DP for resectable pancreatic cancer. This retrospective study examined 139 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…
Background/Aim: The clinical significance of many RAS-family mutations in colorectal cancer (CRC) remains unclear. The purpose of this study was to investigate the relationship of RAS mutations on an exon basis (i.e., mutations in KRAS exons 2,3, and 4 and in NRAS) with clinicopathological features and prognosis in CRC. Patients and Methods: We performed a retrospective cohort study of the medical records and frozen tissue samples of 268 consecutive patients with stage I-III CRC who underwent curative resection at a single institution between 2014 and 2018.
…”
mentioning
confidence: 99%
“…
Background/Aim: The clinical significance of many RAS-family mutations in colorectal cancer (CRC) remains unclear. The purpose of this study was to investigate the relationship of RAS mutations on an exon basis (i.e., mutations in KRAS exons 2,3, and 4 and in NRAS) with clinicopathological features and prognosis in CRC. Patients and Methods: We performed a retrospective cohort study of the medical records and frozen tissue samples of 268 consecutive patients with stage I-III CRC who underwent curative resection at a single institution between 2014 and 2018.
…”
mentioning
confidence: 99%
“…Next, the GNRI was proposed and was used as an age-specific indicator to assess the nutritional status of elderly patients. Surprisingly, recent research has suggested that the GNRI may have better predictive value than nutritional assessment in many diseases, such as heart failure [ 38 , 39 ], hemodialysis [ 40 ], and patients undergoing surgery for various malignancies (for example, colorectal cancer [ 41 ], pancreatic cancer [ 42 ], gallbladder cancer [ 43 ], hepatocellular carcinoma [ 44 ], and esophageal cancer [ 45 ]). A recent study by Chen et al also revealed that the GNRI can be used as a promising alternative to the Global Leadership Initiative on Malnutrition (GLIM) and is the best option for the perioperative management of patients with rectal cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For such occasions, several POPF predictive scores, including inflammatory and/or nutritional status, have been developed, such as the GNRI [ 4 , 5 ], controlling nutritional status score [ 20 ], and prognostic nutritional index [ 22 ] to detect POPF at an earlier phase and with more precision. In addition, those scores using inflammatory or nutritional status, such as GNRI [ 23 ], the platelet-to-lymphocyte ratio [ 24 ], and neutrophil-to-lymphocyte ratio (NLR) [ 25 , 26 ], have been designed as prognostic factors in several types of cancers. Moreover, more recent reports have revealed that NLR, CRP-to-lymphocyte ratio (CLR), CAR, and GNRI play a critical predictive role in the incidence of POCs in pancreatic cancer [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%